A JURIDICAL ANALYSIS OF THE BUSINESS OPPORTUNITY CONCEPT IN COMPARISON WITH THE MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) CONCEPT - Belinda Wijaya; Tristam Pascal Moeliono (RADJA PUBLIKA, 2026)
Large businesses in various countries are required to assist and support Micro, Small, and Medium Enterprises (MSMEs)—known in Indonesia as UMKM—through partnerships. These partnerships can take the form of franchise agreements or other types of agreements. One form of partnership commonly found in business practice is a business opportunity or business package. This paper will examine the form of partnership known as a business opportunity and how the laws in the United States and Indonesia address the development of such collaborations between large-scale businesses and small enterprises (MSMEs or individuals). The research methods employed are normative legal analysis and comparative law. A key finding is that, unlike in the United States, the partnership form giving rise to business opportunity packages—which are not exactly the same as franchise agreements—in Indonesia remains subject to legal practice, meaning it is based solely on contractual freedom. Furthermore, although these business packages resemble partnership agreements between large businesses and SMEs, they differ because they are often formed between investors and individual business activities or even informal ones.